2018
DOI: 10.1111/aos.13700
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on procedures to include in a simulation‐based curriculum in ophthalmology: a national Delphi study

Abstract: The Delphi process identified and prioritized 25 procedures that should be practised in a simulation-based environment to achieve competency before working with patients. The list may be used to guide the development of future training programmes for ophthalmologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Eliminating this transition alone can free up significant time for other aspects of clinical learning and improve clinical efficiency. 5 Interestingly, our study showed that the correlation between the time of ophthalmology exposure during PGY-1 and a perceived improvement to the training experience of residents and preparedness for PGY-2 did not change for cut points beyond 12 weeks. Finally, the study inferred that the number of PGY-1 weeks of ophthalmology training did not appear to influence perception of preparedness for several other factors.…”
Section: Discussionmentioning
confidence: 56%
“…Eliminating this transition alone can free up significant time for other aspects of clinical learning and improve clinical efficiency. 5 Interestingly, our study showed that the correlation between the time of ophthalmology exposure during PGY-1 and a perceived improvement to the training experience of residents and preparedness for PGY-2 did not change for cut points beyond 12 weeks. Finally, the study inferred that the number of PGY-1 weeks of ophthalmology training did not appear to influence perception of preparedness for several other factors.…”
Section: Discussionmentioning
confidence: 56%
“…Overall, we had high response rates as seen in similar studies. [16][17][18][19][20][21][22] In relation to skills in ultrasound, we have noted above that a change in experience and practice might change ranking of ultrasound skills over time. This may also relate to other skills, both those included and not included in the current report, including views on what is feasible in paediatric skill training may thus change over time.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used to develop curricula for simulation-based training in various specialties. [16][17][18][19][20][21][22] The study was conducted from December 2017 to September 2018.…”
Section: Methodsmentioning
confidence: 99%
“…[36][37][38][39][40] There are also successful examples of collaboratives that have developed national simulation curricula in different specialties (e.g., urology in the Netherlands, pulmonary and ophthalmology in Denmark, anesthesia and obstetrics in Canada, vascular and laparoscopic surgery in the United States, and pediatric surgery in France). [41][42][43][44][45][46][47] Future Directions The next steps for the collaborative will involve the development, testing, implementation, and iterative refinement of a curriculum that will cover the described content over a 3-year residency program.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of comprehensive EM residency simulation curricula have been implemented in the United States and abroad showing great potential for this pediatric‐focused work 36‐40 . There are also successful examples of collaboratives that have developed national simulation curricula in different specialties (e.g., urology in the Netherlands, pulmonary and ophthalmology in Denmark, anesthesia and obstetrics in Canada, vascular and laparoscopic surgery in the United States, and pediatric surgery in France) 41‐47 …”
Section: Discussionmentioning
confidence: 99%